Influence of relationships with mothers on romantic relationships of daughters - V. V. Kozyreva; V. A. T. Pham (Вестник университета)
The inﬂuence of mother-daughter relationships on how women build romantic relationships in Vietnam and Russia has been studied. Children often imitate their parents in their thoughts and behaviors, so mothers have an important inﬂuence on the process of shaping daughters’ interaction with the environment. The relationship between mother and daughter represents the help daughter receives from her mother and daughter’s appreciation for her mother. Two techniques were used in the research process: “Questionnaire for determining the type of attachment to mother” by M.V. Yaremchuk and “Trent relationship scales” by E. Scharfe. Attachment in relationships with mothers has a similar vector in romantic relationships. Thus, negative attachment in relationships with mothers leads to negative attachment in romantic relationships, while positive attachment in relationships with mothers leads to positive attachment in romantic relationships. It has been revealed that Russian women have more positive relationships with their mothers than Vietnamese women, which leads them to build more positive romantic relationships.